Endobronchial ultrasound guided transbronchial cryobiopsy versus forceps biopsy in peripheral lung lesions. (19th December 2020) - Torky, Mohamed; Elshimy, Wafaa S.; Ragab, Mohamed AE.; Attia, Ghada A.; Lopez, Raquel; Mate, Jose Luis; Centeno, Carmen; Serra, Pere; Tazi Mezalek, Rachid; Pérez, Eli Nancy; Manzano, Juan Ruiz; Rosell, Antonio; et al.
Abstract: Introduction: Radial probe endobronchial ultrasound (RP‐EBUS) is a modern technique for diagnosis of peripheral lung lesions. It is assumed that the addition of transbronchial cryobiopsy (TBCB) could increase the diagnostic value for RP‐EBUS. Objectives: The main objectives were to evaluate the efficacy and safety of RP‐EBUS‐guided TBCB for diagnosis of peripheral lung lesions and comparing it with RP‐EBUS‐guided transbronchial forceps biopsy. Methods: Sixty patients with peripheral lung diseases were divided into two groups. Group I included 45 patients who were eligible for TBCB and they subjected to forceps transbronchial biopsy (forceps TBB) and TBCB guided by RP‐EBUS. Fifteen patients who were not eligible for TBCB were included in group II and they were subjected to forceps TBB and/or cytology retrieval procedures guided by RP‐EBUS. Results: In group I, forceps TBB had sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of; 67.5%, 100%, 100%, 18.8%, and 69.8%, respectively, while TBCB had sensitivity, specificity, PPV, NPV, and accuracy of 75%, 100%, 100%, 23.1%, and 76.7%, respectively. The sensitivity in group II was 80% and the overall results including both groups were sensitivity, specificity, PPV, NPV, and accuracy of 85.2%, 100%, 100%, 42.8%, and 86.7%, respectively. Regarding the complications, only one patient (1.7%) had significant bleeding. One patient (1.7%) had pneumothorax and another patient (1.7%) suffered from hypoxemia. Conclusions: RP‐EBUS‐guided TBCB is a safe and effective technique for diagnosis of peripheral lung lesions. TBCB has achieved higher diagnostic values and better quality of samples.